Islamic Perspective on Urban Ecology Environmental Preservation in The Context of Urbanization - Fitryansyah, Muhammad Andryan (Pusat Pengkajian dan Pengembangan Islam Jakarta (PPIJ), 2024)
The problem of rapid urbanization has led to environmental degradation in big cities, such as air pollution, reduction of green spaces, and poor waste management. This research aims to examine the role of Islamic perspective in urban environmental conservation. Through the concepts of khalifah (leadership), mizan (balance), and amana (trust), Islamic teachings provide a relevant ethical framework for protecting the environment. This research method is a literature review by analyzing primary sources such as the Qur'an, hadith, and secondary literature related to Islamic ecology and urban environmental challenges. The results show that Islamic teachings offer practical guidance in human interaction with nature. The concept of khalifah places humans as guardians of the earth with the responsibility to preserve the environment. Mizan emphasizes the importance of maintaining the balance of nature, avoiding overexploitation, and ensuring the sustainability of the ecosystem. Meanwhile, amana underlines the moral obligation to manage natural resources responsibly. This research reveals that with the integration of Islamic values, Muslim communities can be more actively involved in urban ecological preservation. The impact of this research is to increase the awareness and participation of Muslim communities in environmental conservation efforts, while enriching the global discourse on sustainability through a holistic approach. In conclusion, Islamic teachings can be a strong foundation in designing more sustainable urban policies, by encouraging a balance between urban development and environmental conservation.